Analisis Kompetensi Manajerial Kepala Madrasah dalam Perencanaan Peningkatan Mutu Pendidikan Madrasah Aliyah Negeri 4 Boyolali - Ali Mubarrok, Muhammad; Bisri, Moh (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The main areas of focus for this qualitative study on the managerial skills of Madrasah heads are planning, implementation, supervision, and barriers to raising the standard of instruction at Madrasah Aliyah Negeri 4 Boyolali. using a method of description. Data were gathered by observation, interview, and documentation approaches; they were then reduced, and presented, and conclusions were drawn from the analysis. The results demonstrate that the vision, mission, goals, and needs of the madrasah are taken into consideration when planning the managerial competency of the madrasah leaders. The head of the madrasah plans the development and enhancement of the madrasah with input from the entire academic community. In work meetings, plans to enhance teacher professionalism are discussed and outlined in the Madrasah's operational and strategic plans. The assessment components of educational supervision include student development, learning goals, syllabus, teacher attendance, and teacher performance in madrasas. The challenge is being able to stay current with technology. As such, this paper advances our understanding of managerialism and managerial competency.